Intraspecific shifts of xerophytic grasses along the leaf economic spectrum in response to long-term vertebrate herbivory - Gorné, L. D. (2018)
Fil: Gorné, L. D. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.